Safety Profile of Bremelanotide Across the Clinical Development Program - Clayton, Anita H; Kingsberg, Sheryl A; Portman, David; Sadiq, Amama; Krop, Julie; Jordan, Robert; Lucas, Johna; Simon, James A (Journal of women's health (Larchmont, N.Y. 2002), 2022)
Bremelanotide, a melanocortin receptor agonist, is Food and Drug Administration (FDA)-approved for the treatment of premenopausal women with acquired, generalized hypoactive sexual desire disorder. Review of bremelanotide's safety profile from the clinical development program (phases 1 through 3). The clinical development program comprised 3500 subjects in 43 completed studies. In the phase 3 studies, subjects took bremelanotide for up to 18 months. The most common adverse events (AEs) were nausea (40.0% vs. 1.3%), flushing (20.3% vs. 1.3%), headache (11.3% vs. 1.9%), and injection site reactions (5.4 vs. 0.5), bremelanotide versus placebo groups, respectively, in the integrated double-blind portion of the phase 3 studies ( = 1247). Nausea was the most common reason for bremelanotide discontinuation. There were no deaths; a few subjects experienced serious AEs. Focal hyperpigmentation was rare when bremelanotide was dosed in accordance with label recommendations, but it occurred in more than one-third of subjects following up to 16 consecutive daily dosings. Small and transient but statistically significant blood pressure increases were observed during ambulatory blood pressure monitoring. Most drug-drug interactions were not clinically significant, except for interactions that lowered plasma concentrations of indomethacin and naltrexone. In the double-blind portion of the integrated phase 3 studies, 70% of the bremelanotide group proceeded to the open-label phase of the studies versus 87% of those on placebo. The AEs associated with bremelanotide are mostly mild to moderate. Although not deemed clinically important, bremelanotide should be used with caution in patients at risk of cardiovascular disease, and blood pressure should be well controlled during treatment. Clinical Trial Registration number: NCT02333071 [Study 301] and NCT02338960 [Study 302].